2016
DOI: 10.1108/ijqss-08-2015-0059
|View full text |Cite
|
Sign up to set email alerts
|

How communicative leadership influences co-workers’ health – a quality management perspective

Abstract: Findings -The result shows concrete communication behavior and methodologies that influence co-worker well-being and the working environment positively and negatively.Another result is a description of the prerequisites for managers to be able to communicate in a way that influences co-worker well-being and the working environment. The analysis of the communication behaviors and communication methodologies versus the health-related Quality Management values shows that several of the health-related Quality Mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
(49 reference statements)
1
16
0
1
Order By: Relevance
“…The majority of authors state that a motivated and prepared worker is the key to operating in sectors with a high degree of contact with the client, which is the case for hotels and restaurants [22][23][24]. In this context, certain authors have demonstrated that the implementation of QMPs can improve staff working conditions as much as it can improve their training and promotion prospects, which, in turn, lead to more motivated and more prepared workers [25][26][27][28].…”
Section: Adoption Of Quality Management and Quality Performance Practmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of authors state that a motivated and prepared worker is the key to operating in sectors with a high degree of contact with the client, which is the case for hotels and restaurants [22][23][24]. In this context, certain authors have demonstrated that the implementation of QMPs can improve staff working conditions as much as it can improve their training and promotion prospects, which, in turn, lead to more motivated and more prepared workers [25][26][27][28].…”
Section: Adoption Of Quality Management and Quality Performance Practmentioning
confidence: 99%
“…Lastly, it is worth noting that the quality facilitates a focus on the customer and continuous improvement [33,34] through long-term supervision in very dynamic surroundings with high degrees of competitiveness, such as the tourism sector. A firm's focus on quality can become a market trend signal [35] and can have positive effects both on current clients, by increasing their loyalty, and on potential clients, by improving their acquisition [27,36]. Many other studies confirm that the implementation of QMPs helps address client needs and adapt to demand [11,26,37].…”
Section: Adoption Of Quality Management and Quality Performance Practmentioning
confidence: 99%
See 2 more Smart Citations
“…In one research study, the dimensions of health-related QM values in relation to the key principles of communicative leadership were examined, and the results show that there is a relationship between the two (Bäckström, Ingelsson and Johansson, 2014b). Another study showed that managers' views of communicative leadership are supported by most of the underlying dimensions of health-related QM values (Bäckström, Ingelsson and Johansson, 2016). A modified and improved version of the survey has been used to measure Lean values and the health-related QM values 'Leadership Commitment' and 'Participation of Everybody' in two manufacturing companies .…”
Section: A Health-related Quality Management Surveymentioning
confidence: 99%